ANALISA EFEKTIVITAS MESIN STEEL CALENDER MENGGUNAKAN METODE TOTAL PRODUCTIVE MAINTENANCE (TPM): ANALYSIS OF EFFECTIVENESS OF STEEL CALENDER MACHINE USING TOTAL PRODUCTIVE MAINTENANCE (TPM) METHOD - Ahmad Zohari (UPPM Akademi Komunitas Semen Indonesia, 2019)
Steel calendar machine is a machine that combines compound and steel became steel treatment and then will be processed on a steel cutting machine to make a steel belt. The steel calender machine used in this process has a high losstime. Therefore, the study was conducted using the total productive maintenance (TPM) method to determine its effectiveness by measuring the Overall Equipment Effectiveness (OEE) and the six big losses. Data collection is taken from barcode sistem material that is carried out for 3 months from January 2018 to March 2018. Given the value of OEE in January 2018 of 43%, February 2018 of 41%, and in March 2018 was 58% for six big losses value is equipment failure losses of 3.32%, set up and adjustment of 22.37%, reduce Speed losses of 2.35%, idling minor and stoppages by 2.01%, defect losses by 0.45%. Based on the analysis, the most dominant losstime for 3 months resulted in low value of OEE is losing size and six big losses in set up and adjustment. In April the engine improves the 4M barcode sistem and the wire up schedule on the machine, and got the OEE value in April of 51% with six big losses of 30%.